Makna Sebagai Tanda - Muhammad Yunis (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2012)
Semiotic explains about meanings and signs. The meanings and signs itself are the two things that are growing and developing from the human’s concept of the universe as a way in defining the life. Comprehending the meaning and sign by Pierce, Barthes, Umberto Eco, or even Piliang concepts will view that those meanings and signs can be interpretated as a life reality which are exist in every relationship of human and God and also human and the nature.